Carotid endarterectomy: A case study and literature review - Tabane, Tebogo; Oosthuizen, Alexis (SA Heart Journal, 2022)
Carotid endarterectomy (CEA) is a preventative surgery that is performed in patient populations at risk of emboli due to an atherosclerotic plaque, located at the carotid bifurcation. Despite the advances in overall treatment, no consensus has been reached on the preferred anaesthetic for CEA. Improved procedural outcomes are due to the advances in medical therapy, cerebral monitoring, improved timing of surgery with improved surgical techniques and the use of ultrasound guided regional techniques. However, the choice of anaesthetic should consider the patient, the hospital’s resources and the preferences of the anaesthesiologist and surgeon. SAHeart 2022;19:20-23